Social Entrepreneurship and Inclusive Growth: Attributes, Perceptions and Roles of Business Incubators and Intermediaries in Malaysia. (November 2019) - Baskaran, Angathevar; Tang, Mingfeng; Thiruchelvam K.; Shahabudin, Sharifah Muhairah; Chan, Theresa S. Y.
Social enterprises are considered to be at the heart of inclusive growth due to their emphasis on people and social cohesion that help effect social and economic transformation. In the Tenth Malaysia Plan (2011–2015), two out of ten objectives are on achieving inclusive growth. In this context, this article explores the ecosystem for social enterprises in Malaysia, raising the following research questions: (a) what are the attributes (features) of business incubators (BIs) and intermediaries (IMs) operating in the social enterprise sector in Malaysia? (b) What are the perceptions of BIs and IMs on various aspects of the social enterprise ecosystem in Malaysia? (c) What is the role of BIs and other IMs in fostering social entrepreneurship (SE) in Malaysia in general and meeting the inclusive growth objective of the country in particular? This study employs the qualitative approach and primary data gathered through interviews of six BIs and IMs and twenty social enterprises. This study found that the current social enterprise ecosystem is weak and still emerging and has yet to take a concrete shape. The absence of legal status for social enterprise is the single most important obstacle in unlocking the potential growth of social enterprise sector. This study suggests that the government initiates policy measures to give legal status to social enterprises in the country, in order to develop the ecosystem and facilitate a greater participation of the private sector.